The effectiveness of condoliase therapy for lumbar disc herniation - Ide, Koichiro; Yamada, Tomohiro; Arima, Hideyuki; Banno, Tomohiro; Kurosu, Kenta; Yamato, Yu; Watanabe, Yuh; Hasegawa, Tomohiko; Oe, Shin; Matsuyama, Yukihiro; Yoshida, Go (Journal of Spine Research, 2024)
Introduction: The aim of this study was to investigate the frequency of significantly effective cases, where pain almost disappeared, and the associated factors in condoliase therapy for lumbar disc herniation (LDH). Methods: We enrolled 93 cases (61 males, 32 females, average age 45.6 years) that underwent condoliase therapy for LDH with minimally follow-up of 1 year. Clinical evaluations, including Oswestry Disability Index (ODI) and Visual Analog Scale (VAS) for back pain and leg pain, and imaging assessments using MRI were conducted before and 1 year after the treatment. Cases with leg pain VAS≤1 cm at 1 year were considered significantly effective and were compared with non-significantly effective cases. Additionally, multivariate analysis was performed to identify risk factors.Results: Surgical treatment was subsequently required in 13 (14.0%) patients, and significantly effective in 49 (52.7%) patients. The rate of females and history of discectomy at the same level were significantly higher in non-significantly effective cases. Moreover, the symptom duration was significantly longer. Multivariate analysis identified symptom duration as independent associated factors.Conclusions: Chemonucleolysis with condoliase was significantly effective in 52.7% of cases. Significant therapeutic effects can be expected in cases with shorter symptom duration.